Bolivia : Fourth Review Under the Stand-By Arrangement and Request for Waiver of Nonobservance of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2004)
This paper discusses Bolivia's Fourth Review Under the Stand-By Arrangement (SBA) and Request for Waiver of Nonobservance of Performance Criteria (PC). Economic activity in Bolivia is picking up, led by exports. Real GDP growth is projected to reach 3.8 percent in 2004. Inflation has increased but remains in low single digits. The current account surplus increased, although recent capital outflows more than offset the improvement. The 2004 program is broadly on track. Fiscal quantitative performance criteria (PCs) at end-June were also observed.